Analysis of the Factors Leading to the Degradation of Wooden Cultural Heritage Based on the Example of a 16th-Century Sacred Monument in Poland - Bogusław Andres; Izabela Betlej; Małgorzata Nowacka; Piotr Boruszewski (Applied Sciences)
Microorganisms are one of the most critical factors involved in the degradation of buildings. Fungi that develop in historic spaces not only cause the degradation of monuments (immovable and movable) but can also negatively affect those who visit or use such spaces. This article is a case study of the 16th-century St. Catherine Church in Cięcina (Poland), whose walls became severely damp as a result of changes made to the church’s surroundings (relocation of the riverbed of the Cięcinka River, raising the level of St. Catherine Street and building a wooden fence on a concrete foundation around the church). The effect of the severe dampness of the building was the intensive development of Serpula lacrymans fungus and mold. This article highlights the importance of a multidisciplinary approach to hazard diagnosis in historic buildings.